Modernizing IT Infrastructure in Academia: A Case Study from AGH University of Krakow - Konrad ZAWORSKI (Communications of International Proceedings, 2025)
Modern universities increasingly depend on unified IT infrastructures that can support teaching, laboratory work, and remote access. Fragmented systems, inconsistent laboratory environments, and limited identity management, significantly reduce usability for students and create administrative overhead. To address these challenges, a modernization project was initated at the Department of Applied Computer Science at AGH University of Krakow. Although prior studies discuss identity management or digital transformation in higher education, there is limited documentation of fully integrated, department-level infrastructure reform carried out using only open-source technologies and limited resources. This paper fills that gap by presenting a practical case study, offering a replicable model for institutions seeking cost-effective modernization. The project unified identity and access management with FreeIPA, standardized laboratory environments using automated deployment via Ansible and Kickstart, and introduced a virtualization platform based on QEMU/KVM with customized image distribution and VM management tool. Department Panel was developed as the central user interface integrating public services. The evaluation method included a survey of 100 students actively using the new environment. Results demonstrate very high user satisfaction. Students strongly indicated that the availability of modern IT services positively influences their learning experience and could shape their choice of university.
Keywords: academic environment; open source; IT infrastructure; identity management; virtualization